Size and structure of freely forming conversational groups - Dunbar, R; Duncan, N; Nettle, D (Walter de Gruyter, Inc. New York, 1995)
Data from various settings suggest that there is an upper limit of about four on the number of individuals who can interact in spontaneous conversation. This limit appears to be a consequence of the mechanisms of speech production and detection. There appear to be no differences between men and women in this respect, other than those introduced by women's lighter voice.